Composite Adaptive Antidisturbance Control for Discrete-Time Switched System - Haibin Sun; Qiang Lu; Linlin Hou (Discrete Dynamics in Nature and Society)
A novel composite adaptive antidisturbance controller is developed for a class of discrete-time switched system. First, two composite adaptive observers are proposed to estimate the external disturbances and unknown parameters, respectively. Then, based on the estimation values, a composite adaptive antidisturbance controller is constructed, which can guarantee system has a good antidisturbance performance. A solvable sufficient condition is presented by using linear matrix inequalities (LMIs). Finally, a numerical example is shown to demonstrate the effectiveness of the proposed control approach.